Aplicación De Herramientas De Administración Financiera, A La Mueblería Interamericana En La Ciudad De Loja, Periodos 2010 – 2012 - Pineda Sánchez, Margeory (2016)
This work called "APPLICATION OF FINANCIAL MANAGEMENT TOOLS TO THE AMERICAN MUEBLERIA IN THE CITY OF Loja, PERIOD 2010 - 2012", aims to apply financial management tools to its financial statements for them based on managers to make decisions that contribute to the growth of the company, for efficient enterprise resource management. To carry out the research work was necessary, the presentation of objectives in order to determine the financial structure of the company both past, present and future, as well as analyze their liquidity ratio of profitability and debt of the company, which allows me see how your financial situation is and thus be able to project their balance sheets for the next financial period. Among the objectives is the implementation of vertical analysis that allowed us to observe that the furniture has a working capital volume which is an endorsement of his possessions the furniture to its creditors. The second objective is the application of horizontal analysis, where the furniture has the ability to cover its short and long term, due to revenue from sales has had in his three years, however the cost related to Information this is extremely high which does not allow them to be more competitive and therefore this causing the maintenance of high inventory investment. The third objective is the application of financial reasons, where the company is committed to low rate with your creditors because the furniture I have a high index of liquidity which is bad not because it allows you to generate profitability and thus grow in the market, despite its high cost of sales, the furniture has the ability to make a profit and still achieve the investment company Like other objectives of both the equilibrium point and the projection of the cash budget for the two years we show optimal cash flows means that cash receipts will enable it to cover its costs. In their proformas few states shows that the furniture will have a positive working capital which is beneficial because it will stay in the market. Three proposals for improvement that will allow the proper administration of the financial resources of the furniture are also established. Finally conclusions and recommendations that will enable the owner to improve their actions in the market down.